2017
DOI: 10.1097/ftd.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Mycophenolic Acid Area Under the Curve With Limited-Sampling Strategy in Chinese Renal Transplant Recipients Receiving Enteric-Coated Mycophenolate Sodium

Abstract: Background:The enteric-coated mycophenolate sodium (EC-MPS), whose active constituent is mycophenolic acid (MPA), has been widely clinically used for organ transplant recipients. However, its absorption is delayed due to its special designed dosage form, which results in difficulty to monitor the exposure of the MPA in patients receiving the EC-MPS. This study was aimed at developing a relatively practical and precise model with limited sampling strategy to estimate the 12-hour area under the concentration–tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…Some researches have shown that the trough level of MPA may be correlated to the patient’s outcomes in kidney transplant recipients ( Borrows et al, 2006 ; Miura et al, 2011 ). However, many studies have indicated a poor correlation between single-point concentrations and MPA-AUC 0-12 h ( Barraclough et al, 2012a ; Chaabane et al, 2013 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ; Jia et al, 2017 ). The present study also revealed the same result.…”
Section: Discussionmentioning
confidence: 99%
“…Some researches have shown that the trough level of MPA may be correlated to the patient’s outcomes in kidney transplant recipients ( Borrows et al, 2006 ; Miura et al, 2011 ). However, many studies have indicated a poor correlation between single-point concentrations and MPA-AUC 0-12 h ( Barraclough et al, 2012a ; Chaabane et al, 2013 ; Yamaguchi et al, 2013 ; Cai et al, 2015 ; Jia et al, 2017 ). The present study also revealed the same result.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately calculate it, at least 10 blood samples much be collected over 12 hours; thus, this method is costly and difficult to adopt, especially in outpatient departments. As such, limited sampling strategies and pharmacokinetic models have emerged that are simpler to use to estimate the MPA AUC in such settings [ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous report (12)(13)(14), the patients were randomly assigned to two groups at a 1: 1 ratio: the model group (n = 23) and the validation group (n = 22). An AUC0-12 prediction formula was derived using multiple regression analysis with the model group AUC0-12 as a dependent variable and the plasma concentration at each blood sampling time as an explanatory variable.…”
Section: Discussionmentioning
confidence: 99%